Printing bone in a gel: using nanocomposite bioink to print functionalised bone scaffolds. (September 2019) - Cidonio, G.; Cooke, M.; Glinka, M.; Dawson, J.I.; Grover, L.; Oreffo, R.O.C.
Abstract: Free-form printing offers a novel biofabrication approach to generate complex shapes by depositing hydrogel materials within a temporary supportive environment. However, printed hydrogels typically lack the requisite mechanical properties and functionality of the desired tissue, limiting application and, more importantly, safety and efficacy of the implant. The study authors have developed an innovative nanoclay-based bioink to print high shape fidelity functional constructs for potential skeletal application. Laponite® (LAP) nanoclay was combined with gellan gum (GG) to generate a printable hydrogel that was highly stable in vitro, displayed limited swelling ability compared with the silicate-free control and remained stable over time. An agarose fluid gel was found to provide the requisite support for the deposition of the material ink and preservation of the printed structure before crosslinking. Printed C2C12 myoblasts remained viable and displayed extensive proliferation over 21 days in culture. Cell-laden scaffolds demonstrated functionality within 1 day of culture in vitro and that was preserved over 3 weeks. Analysis of absorption and release mechanisms from LAP-GG using model proteins (lysozyme and bovine serum albumin) demonstrated the retention capability of the clay-based materials for compound localisation and absence of burst release. Vascular endothelial growth factor ​was loaded within the agarose fluid gel and absorbed by the material ink via absorption during deposition. The 3D-printed constructs were implanted on the chorioallantoic membrane of a 10-day-old developing chick. Extensive and preferential vasculature infiltration was observed in LAP-GG–loaded vascular endothelial growth factor constructs compared with controls ( p <0.01 and p <0.0001) after only 7 days of incubation. The current studies demonstrate, for the first time, the application of innovative LAP-GG 3D constructs in the generation of growth factor–loaded 3D constructs for potential application in skeletal tissue repair. Graphical abstract: LAP-GG printing in agarose fluid gel for skeletal tissue engineering. Extrusion of LAP-GG in an agarose bed to generate three-dimensional structures (a). Low polymeric content nanosilicate bioink was used to deliver cells and preserve their viability after extrusion. Agarose fluid gel was harnessed to enable loading of compounds of interests during printing (b) in LAP-GG and GG controls. LAP-GG bioink offers the potential for enhanced compound penetration within the printed strand. LAP-GG extrusion within self-healing agarose can be used to fabricate large functional structures (c) such as 3D sleeve (i and ii) and 3D lattice (iii and iv) structures to fill critical bone defects. Cells were printed in LAP-GG (d) and viability (i and ii) and functionality (iii and iv) were assessed for skeletal tissue formation potential. Integration with chick membrane model and vascular penetration (e) of printed scaffolds implanted within the vascularised membrane of a developing chick. Scale bar: (a) 5 ​mm, (b—i and ii) 100 ​μm, (c—i and ii) 30 ​mm, (c—iii) 30 ​mm, (c—iv) 10 ​mm, (d—i) 100 ​μm, (d—iii and iv) 2 ​mm. Image 1